Retrospeksi Ekonomi-Politik Kebijakan Pemberantasan Kemiskinan di Pedesaan - Victor A Hamel (Magister Ilmu Administrasi Publik, 1999)
Using a political-economy model of analysis introduced by Uphoff and Ilchman (1972), the writer tries to analyze the